Reliability Criteria in Source Coding Problem with Secret Component - Haroutunian, Mariam E.; Santrosyan, Jemma S.; Hakobyan, Parandzem M. (Mathematical Problems of Computer Science, 2025)
This work addresses a source coding problem for one-way sources with correlated outputs. In this scenario, one source output must be transmitted to the receiver within a specified distortion level, similar to conventional source coding. Simultaneously, the other source output must be kept as confidential as possible from the receiver or a potential wiretapper. For this model, the rate-reliability-distortion-equivocation function and the equivocation-reliability-distortion function are defined and analyzed.